Norfloxacin Cocrystals: Mechanochemical Synthesis and Scale-up Viability Through Solubility Studies - Ferreira, Patricia O. [UNESP]; de Almeida, Amanda C. [UNESP]; Costa, Giovanna de P. [UNESP]; Torquetti, Carolina [UNESP]; Baptista, João A.; Eusébio, M.Ermelinda S.; Caires, Flavio J. [UNESP]; Castro, Ricardo A.E. (Elsevier, 2023)
Cocrystals are recognized as one of the most efficient approaches to improve aqueous solubility of Biopharmaceutical Classification System, BCS, classes II and IV drugs. Cocrystal discovery and the establishment of experimental conditions suitable for scale-up purposes are some of the main challenges in cocrystal investigation. In this work, the investigation of mechanochemical synthesis of norfloxacin cocrystals with picolinic and isonicotinic acids is performed, leading to the discovery of two new cocrystals of this important BCS class IV antibiotic, which were characterized through thermal, spectral and diffractometric analysis. Norfloxacin apparent aqueous solubility using the cocrystals is also presented, with higher values being obtained for all the investigated systems when compared to the pure drug. Norfloxacin has 3 polymorphs and several solvents/hydrates, which represents a challenge for obtaining pure cocrystal forms from solvent crystallization. This challenge was successfully overcome in this work, as experimental conditions to obtain the pure cocrystals (the new ones and also norfloxacin-nicotinic acid and norfloxacin-saccharin) were established using Crystal16 equipment. This is a crucial step to envisage future scale-up procedures and therefore a valuable information for the pharmaceutical industry.
Keywords: Cocrystal; Mechanochemical synthesis; Norfloxacin; Scale-up; Solubility studies; Ternary phase diagram